Evaluación clínica del comportamiento de materiales restauradores en molares primarios - Brasca, Nora; Urquía-M., María del Carmen (Revista Facultad de Odontología Universidad de Antioquia, 2020)
The objective of this study was to evaluate the clinical and in vitro behavior of restorative materials in primary teeth. A cohort of 70 patients (aged 6 -7) was evaluated. They received a total of 102 restorations with class I cavity preparation in the upper and lower second primary molars. The group was randomly divided into 6 groups according to the material to be used in the restoration: Group I: conventional amalgam (Ventura Cap, Macrodent S.A.); Group II: Adhesive Amalgam (S.B.M.P.P., 3 M, St. Paul MN, USA); Group III: Composite resin (Z 100, 3 M, St. Paul MN, USA); Group IV: Cermet (Ketac Silver; Espe, Seefeld Germany); Group V: Resin-modified glass ionomer cement Vitro (Vitremer, 3 M., St. Paul MN, USA); Group VI: Compomer (Compoglass, Vivadent, Schaan, Liechtenstein ). The restoration were evaluated at 6,12,18, 24 and 30 months according to Ryge criteria regarding anatomic form, marginal adaptation, marginal pigmentation, color stability and post-operative sensitivity. In regard to anatomical form 81,41% of the restorations were classified Alpha at 30 months. The Chi-square test showed that there were significant differences in the percentages of Alpha samples belonging to Group IV and the other groups (X2 = 23,754; P < 0,0005); however, these differences did not appear among Groups I, II, III, V and VI. For marginal adaptation, marginal decoloration and color stability, there were no significant differences among the percentages of Alpha specimens for the different materials. As it regard the post-operative sensitivity, there were important significant differences between Groups I, III and IV and Groups IL V and VI. It can be concluded that restorative materials with adhesive technology are suitable for the restoration of primary teeth until their natural exfoliation time.